Implementasi V-Model dengan Business Intelligence untuk Sistem Informasi Manajemen Penjualan dan Inventori Obat di Apotek Madani - Ichsandi Ichsandi; Rolly Gios Sholid; Widja Yanto; Mulia Aminurahman; Siti Nurlaela (Pusat Riset dan Inovasi Nasional, 2026)
Drug sales and inventory management at Madani Pharmacy still relies on manual processes, potentially leading to recording errors, inefficient stock management, and limitations in obtaining analytical insights to support decision-making. This study aims to implement the V-Model in the development of a Drug Sales and Inventory Management Information System (SIMPIO). The system analysis and design stages are modeled using Unified Modeling Language (UML), including use case, activity, class, and sequence diagrams to systematically describe actors, process flows, data structures, and interactions between modules. SIMPIO is integrated with Business Intelligence (BI) to provide real-time data visualization in the form of stock reports, sales trends, and drug demand predictions through an interactive dashboard. System testing was conducted using the blackbox method. The results showed that the system runs effectively with a user satisfaction level reaching 90%, increasing inventory accuracy by up to 95%, accelerating transaction times, and optimizing operations and managerial decision-making at Madani Pharmacy.